THE RELATIONSHIP BETWEEN PEER SUPPORT SYSTEM AND STRESS LEVEL OF WORKING ON A THESIS FOR S1 NURSING STUDENTS OF STIKES MEDISTRA INDONESIA IN 2023 - Novi Pangestuti; Puji Raharja Santosa; Kiki Deniati (Jurnal Medicare, 2023)
Final year students often experience stress with a undergraduate thesis, one of which is nursing students who are working on a undergraduate thesis. Support systems are people who have energetic and functional help have been shown to be healthier than people without support. Support system is about telling others that they are loved and cared for, that they have self-esteem and are valued both verbally and non-verbally.. Type of quantitative research with cross sectional method. Population with a total of 99 respondents. Sampling technique using random sampling sample. Based on the results  of chi-square  test analysis with a value of  p = 0.001  (p < 0.050) so that it is stated that H0 is rejected. Based on the results of statistical analysis using  the chi square test, it can be concluded that H0 is rejected, which means that there is a relationship between  peer support system and the stress level of doing a undergraduate thesis in S1 nursing students at STIKes Medistra Indonesia in 2023.